DAMPAK KECANDUAN GAME ONLINE TERHADAP AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN PPKn KELAS VIII SMP NEGERI 1 TOMA - Kartika Kristiani Lature (Universitas Nias Raya, 2024)
The background to this research problem is that online game addiction has an impact on student learning activities. The research objectives are 1) To find out and describe the impact of students' online game addiction on students' learning activities in class VIII Civics subjects at SMP Negeri 1 Toma for the 2023/2024 academic year. 2) To find out and describe how students' learning activities are in the Civics class VIII subject of SMP Negeri 1 Toma for the 2023/2024 academic year. This research uses qualitative research. The research subjects were class VIII students. Research results 1) Addiction to online games has an impact on students' learning activities, because if they are addicted it will be difficult to leave online games, so students who are addicted to online games will disrupt student learning activities 2) Learning activities of students who are addicted to online games and those who are not addicted to online games At school it is very different, those who are addicted to online games often seem sleepy during the learning process, often don't do their homework, are often late for school, and don't concentrate on studying. The conclusion of the research is that addiction to online games has a negative impact on students' learning activities in Class VIII Civics subjects at SMP Negeri 1 Toma for the 2023/2024 academic year. Researchers provide several suggestions, namely 1) Students should reduce playing online games at home, at school and in the community by filling their free time with useful things such as studying or reading textbooks. 2) Teachers should carry out learning that improves students' cognitive abilities, by increasing learning activities that involve students taking an active role in groups, and providing education about the negative impacts caused by addiction to playing online games.